The problems caused by the lack of project compatibility in the executive process of a metallic structure (Research, Society and Development, 2022)
Compatibility aims to unify projects in a work, facilitating execution, mitigating structural changes that occur during construction, reducing maintenance costs and constructive difficulties that may appear in progress, in addition to maintaining final customer satisfaction. When analyzing the failures caused by the lack of compatibility, ways are imagined to reverse the problems obtained when the work is in progress, however, when dealing with a metallic structure, there are more adversities in the process - since these do not allow many adaptations in its primary structure (columns and beams) as a result of its dimensioning being all planned with its locations and load capacities already predetermined, making it difficult, but not impossible, any type of alteration in the execution. Thus, this research aims to analyze the problems caused in executive processes of metallic structures when their projects are not compatible, characterized and exemplified with cases found in buildings. The methodology is qualitative, an analysis through a case study made with a single metallic building. Among the results, problems were identified due to changes in the architecture and details requested by the owner when the assembly process was already in progress, in addition to the lack of compatibility between the projects that caused rework, time and additional resources to the construction. Concluding, therefore, that the execution process should only be started when the projects are defined, with all the compatibilizations between them duly carried out.